Sir Thomas Mostyn and John Lydgate's Th Lyf of Our Lady : a Middle English Devotional Work and Its North Walian Afterlife. (1st June 2022) - Niebrzydowski, Sue
The library of Sir Thomas Mostyn, second baronet (1651– 92) at Gloddaith Hall (Llandudno), is recognised as the most significant private collection of manuscripts made in Wales. Among Sir Thomas's medieval treasures were manuscripts of English provenance – some written in Middle English – one of which is Sir Thomas's copy of John Lydgate's devotional work, The Lyf of Our Lady. This article examines what the purchase of Lydgate's Lyf reveals about Sir Thomas's principles of acquisition of medieval English manuscripts. Sir Thomas's copy of the Lyf was not the only copy of this work of Marian devotion owned by the Mostyn family. Reading Lydgate's Lyf in conjunction with an early seventeenth-century recusant missal in circulation in the Holywell area suggests an unlooked-for afterlife for John Lydgate's Lyf and the post Reformation devotion of the Mostyn family in the environs of Holywell.